Surface Grafting via Photo-Induced Copper-Mediated Radical Polymerization at Extremely Low Catalyst Concentrations - Laun, Joachim; Vorobii, Mariia; de los Santos Pereira, Andres; Pop-Georgievski, Ognen; Trouillet, Vanessa; Welle, Alexander; Barner-Kowollik, Christopher; Rodriguez-Emmenegger, Cesar; Junkers, Thomas (Macromolecular rapid communications., 2015)
Surface‐initiated photo‐induced copper‐mediated radical polymerization is employed to graft a wide range of polyacrylate brushes from silicon substrates at extremely low catalyst concentrations. This is the first time that the controlled nature of the reported process is demonstrated via block copolymer formation and re‐initiation experiments. In addition to unmatched copper catalyst concentrations in the range of few ppb, film thicknesses up to almost 1 μm are achieved within only 1 h. Surface‐initiated photo‐induced copper‐mediated radical polymerization is employed to graft a wide range of polyacrylate brushes from silicon substrates at extremely low catalyst concentrations. Block copolymer formation and re‐initiation experiments evidence good control over the reaction. In addition to unmatched copper catalyst concentrations in the range of few ppb, film thicknesses up to almost 1 μm are achieved within only 1 h.